Factors affecting motorcyclist accident: psychological, environmental and vehicle factors - Mohd Nusa, Fatin Najwa; Ishak, Siti Zaharah; Abdull Rahman, Siti Hamidah; Awang, Zulkifli; Mohamad, Mimi Mohaffyza (2021)
The highest contributor to road accidents and fatality in Malaysia involves motorcyclists. Recognizing this fact, identifying the issues that cause motorcyclists’ accidents is essential for the government to develop appropriate road safety strategies to address the problem. Factors associated with motorcyclist accidents are generally related to motorcyclist riding behavior, road engineering and environments, and vehicle factors. Possible reasons that caused motorcyclist fatalities are riding above the speed limit, breaking traffic lights, following other vehicles closely, and the negligence of riders. This paper aims to identify the main factors affecting fatal accidents among motorcyclists from the perspectives of 146 road transport officers’ ranking from the high to low order. Respondents involved in this study are staff and officers who serve in the Malaysian Road Transport Department. This study adopted the Theory of Planned Behavior (1985) and other factors influencing motorcyclists’ attitudes and behaviors. Using Microsoft Excel, frequency analysis was used to rank all factors associated with motorcyclist accidents in the questionnaire survey. Findings show that psychological factors were the main factors affecting motorcyclist accidents.